Nursing of a patient with herpes zoster treated by integrated traditional Chinese and western medicine (中西医结合治疗1例带状疱疹患者的护理体会) - RUAN Na (阮娜); CHEN Lu (陈璐); GUO Xinyi (郭新一); ZHANG Xinyu (张欣宇); GENG Miaomiao (耿苗苗); SUN Mingli (孙明丽) (中西医结合护理)
This paper summarized the Traditional Chinese Medicine (TCM) nursing technology for a patient with pain due to herpes zoster. Under the guidance of TCM syndrome differentiation and nursing assessment, TCM nursing technology such as collapse stains, cupping, auricular acupoint sticking and pressing were carried out, working collaboratively with antiviral and analgesic therapy, to relieve the pain and other clinical symptoms of herpes zoster. (本文总结1例带状疱疹水疱并引起疼痛的患者实施中医护理技术相关经验。首先根据患者情况辨证分型, 做好护理评估, 然后根据证型实施中药溻渍、耳穴压豆、拔火罐等中医干预措施, 同时结合西医抗病毒、止痛治疗和常规护理干预。中西医相互补充, 互起协同作用, 能更有效改善患者皮肤不适症状, 缓解疼痛。)